Equity in access to total joint replacement of the hip and knee in England: cross sectional study. - Judge, A; Welton, N; Sandhu, J; Ben-Shlomo, Y (2010)
OBJECTIVE: To explore geographical and sociodemographic factors associated with variation in equity in access to total hip and knee replacement surgery. DESIGN: Combining small area estimates of need and provision to explore equity in access to care. SETTING: English census wards. SUBJECTS: Patients throughout England who needed total hip or knee replacement and numbers who received surgery. MAIN OUTCOME MEASURES: Predicted rates of need (derived from the Somerset and Avon Survey of Health and English Longitudinal Study of Ageing) and provision (derived from the hospital episode statistics database). Equity rate ratios comparing rates of provision relative to need by sociodemographic, hospital, and distance variables. RESULTS: For both operations there was an "n" shaped curve by age. Compared with people aged 50-59, those aged 60-84 got more provision relative to need, while those aged >or=85 received less total hip replacement (adjusted rate ratio 0.68, 95% confidence interval 0.65 to 0.72) and less total knee replacement (0.87, 0.82 to 0.93). Compared with women, men received more provision relative to need for total hip replacement (1.08, 1.05 to 1.10) and total knee replacement (1.31, 1.28 to 1.34). Compared with the least deprived, residents in the most deprived areas got less provision relative to need for total hip replacement (0.31, 0.30 to 0.33) and total knee replacement (0.33, 0.31 to 0.34). For total knee replacement, those in urban areas got higher provision relative to need, but for total hip replacement it was highest in villages/isolated areas. For total knee replacement, patients living in non-white areas received more provision relative to need (1.04, 1.00 to 1.07) than those in predominantly white areas, but for total hip replacement there was no effect. Adjustment for hospital characteristics did not attenuate the effects. CONCLUSIONS: There is evidence of inequity in access to total hip and total knee replacement surgery by age, sex, deprivation, rurality, and ethnicity. Adjustment for hospital and distance did not attenuate these effects. Policy makers should examine factors at the level of patients or primary care to understand the determinants of inequitable provision.